Isolate variations in Colletotrichum gloeosporioides infecting pomegranate (The Journal of Plant Protection Sciences, 2024)
Eleven pomegranate varieties were tested against six isolates of Colletotrichum gloeosporioides under controlled  conditions. Inoculated fruits were assessed on the basis of virulence of the isolates and reaction of a particular  variety was expressed in Disease Reaction Index (DRI). There was considerable variation in virulence and suscep tibility within isolates and varieties. Isolate Cg 86 was found to be virulent (DRI 7.2), Cg 81 as less virulent (DRI  2.87), and other isolates were moderately virulent irrespective of varieties. Fruit varieties Aarakta and Bhagwa  were found to be highly susceptible as both displayed maximum mean DRI 10.38 and 8.56, respectively irrespec tive of isolates. Resistant varieties Yarcud local and Bedana thin skin showed uniform resistant reaction against  six isolates of the pathogen. The interaction between isolates x varieties was also statistically significant. Highest  DRI (15.22) was recorded in the interaction between Bhagwa x Cg 85 and it was on par with Ganesh x Cg 86,  Aarakta x Cg 82, Aarakta x Cg 84, Ruby X Cg 86, Patna 5 X Cg 86 and Patna 5 X Cg 82.
Keywords: pomegranate; Colletotrichum gloeosporioides; disease reaction index; isolate; varieties